AB0243 The Importance of Biomarkers (RF, ACPA and MMP-3) Serum Levels of Rheumatoid Arthritis (RA) in Prediction Bone Erosions in Patients with Early RA and No Visible Radiographic Structural Damages-An Echosonographic Study. (15th July 2016) - Prodanovic, S.Z.; Radunovic, G.; Sefic-Bukilica, M.; Seric, S.; Damjanov, N.
Abstract : Background: Rheumatoid factor (RF) and autoantibodies against citrullinated peptides/proteins (ACPA) has been recognized as an important predictor of more severe structural joint damage. Baseline matrix metalloproteinases 3 (MMP-3) serum levels were described as a predictor for the development of joint erosions.Ultrasonography is more sensitive than X-ray in detecting erosions in RA. Objectives: to assess the importance of the RF, ACPA and MMP-3 serum levels in prediction of hands and feet bone erosions, detected by ultrasound (US) examination, in patients with early rheumatoid arthritis, without structural damage visible on X-ray. Methods: A group of 65 patients (56 female, mean age 53.8±14.6 yrs.) with early RA (Eular/ACR 2010 classification criteria) and ≤1 year duration, (mean duration 3.8 month), were enrolled in the cross sectional clinical study. All patients had been disease-modifying anti-rheumatic drug (DMARDs) and glicocorticoid therapy naïve and had no visible structural damage on hands and feet X-ray. The serological markers of RA were measured: RF (normal concentration<16 U/ml), ACPA (normal concentration<20 IU/ml) and total MMP-3 (normal cut-off range for females: 18–60 ng/ml and males: 24–120 ng/ml). The levels above normal were reted as positive. Ultrasound examination of both hand (wrist, MCP2, MCP5 joints) and MTP5 joints was performed by Esaote My Lab 70 machine using 18 MHz linear probe. Findings of bone erosion were determined according to OMERACT US group definition. Collected data were analyzed in SPSS 16 system. Results: Joint bone erosions were found in 59 (90.8%) pts. by US examination. Forty-two (64.6%) pts. were RF positive (mean concentration 88.8±108.2). The mean 2.1 vs.1.6 US bone erosions were detected in RF positive in comparison to RF negative pts. respectively. Forty-six (70.7%) pts. were ACPA positive (mean concentration 467.0±454.4) with mean bone erosions 1.9 vs.1.8 bone erosions in ACPA negative pts. Forty-six out of 63 (73.0%) pts were MMP-3 positive (mean concentration 185.1±241.0) with mean bone erosions 2.1 vs.1.5 bone erosions in MMP-3 negative pts. The 0.500 value of the area under the ROC curve is found for RF, 0.443 for ACPA and 0.627 value for MMP-3. The 75.4% sensitivity, 67% specificity (cut of 99.2 ng/ml) of MMP-3, 71.9% sensitivity, 50% specificity (cut of 232 IU/ml) of ACPA and 66.7% sensitivity, 67% specificity (cut of 79.5 U/ml) of RF were established in predicting US bone erosion. Conclusions: Early RA patients with no visible structural damages on X-ray, and increased RF, ACPA and MMP-3 serum levels had higher number of bone erosions assessed by US. Baseline MMP-3 serum levels had the highest sensitivity in predicting joint bone erosions assessed by ultrasound examination. Disclosure of Interest: None declared